Differences in Dynamics between Crosslinked and Non‐Crosslinked Hyaluronates Measured by using Fast Field‐Cycling Relaxometry. Issue 13 (11th August 2015) - Ravera, Enrico; Fragai, Marco; Parigi, Giacomo; Luchinat, Claudio
Abstract The dynamic properties of water molecules in gels containing linear and crosslinked hyaluronic acid polymers are investigated by using an integrated approach that includes relaxometry, solid‐state NMR spectroscopy, and scanning electron microscopy. A model‐free analysis of field‐dependent nuclear relaxation is applied to obtain information on mobility and the population of different pools of water molecules in the gels. Differences between linear and crosslinked hyaluronic acid polymers are observed, indicating that crosslinking increases both the fraction and the correlation time of water molecules with slow dynamics.